Governance dalam Manajemen Konflik Pemanfaatan Danau Maninjau - , Roza Syafdefianti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Managing public dispute of Lake Maninjau has been taking place for a long time, from 1998 untill 2010. A lot of efforts has been done in managing this conflict, from arranging a meeting for governance stakeholders to formulation of the management of Lake Maninjau by the local government, but had not been able to provide a conflict resolution agreed by all parties. Vice versa, the conflict was increasingly protracted. By using qualitative method, this research tries to describe the mechanisms and initiatives of conflict resolution held by the governance. Theories that is used to analyze the phenomenon of Lake Maninjau's conflict are public dispute, public policy, and the concept of governance as a conflict management. The conclusion from this research is the lack of capability of governance stakeholders in managing public dispute of Lake Maninjau caused the mechanism of public dispute of Lake Maninjau less successful. It can be seen from the lack of capability of governance in identifying problems, and the absence of conflict resolution and policy recommendation agreed by consensus, thus, indicates the conflict will be re-escalate. Based on the condition, a new conflict resolution mechanism is formulated as new problem solving of Lake Maninjau's conflict. Also important factors in this conflict resolution are alternatives of community economic empowerment and regulation that is regulating a comprehensive lake management.